2023
DOI: 10.1002/14651858.cd011019.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation for people with low vision

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A potential way to offer assessment and additional training is via telerehabilitation using a video visit encounter, but there is limited evidence available to support the efficacy of a remote training modality. 18 Preliminary data support that additional training via telerehabilitation can improve self-reported magnifier use, 19 near reading acuity with magnifiers, and near reading speed at the reading acuity level. 20 It is important for future research to gain a better understanding of real-world reading challenges in the home environment that can be observed during telerehabilitation, which affect extended reading.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A potential way to offer assessment and additional training is via telerehabilitation using a video visit encounter, but there is limited evidence available to support the efficacy of a remote training modality. 18 Preliminary data support that additional training via telerehabilitation can improve self-reported magnifier use, 19 near reading acuity with magnifiers, and near reading speed at the reading acuity level. 20 It is important for future research to gain a better understanding of real-world reading challenges in the home environment that can be observed during telerehabilitation, which affect extended reading.…”
Section: Discussionmentioning
confidence: 86%
“…Future studies will need to assess whether additional handheld optical magnifier training can improve reading speed among those who did not improve in our study. A potential way to offer assessment and additional training is via telerehabilitation using a video visit encounter, but there is limited evidence available to support the efficacy of a remote training modality 18 . Preliminary data support that additional training via telerehabilitation can improve self-reported magnifier use, 19 near reading acuity with magnifiers, and near reading speed at the reading acuity level 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true for elderly patients who may also have visual impairments and for patients with significant disabilities who may have associated cognitive impairments. While research in this area has shown promise, it is essential to continue evaluating and refining these technologies to ensure their clinical quality and effectiveness compared to traditional face-to-face rehabilitation [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of a rigorous evidence basis for telerehabilitation involving magnification device training for low vision; randomized controlled trials have not yet been conducted. 7 , 8 Skills taught by providers in office may not carry over when patients use magnifiers at home if the lighting, working distance, viewing angle, and/or ergonomics are not ideal. Additionally, patients may not retain the specific instructions that are essential to improve reading ability with magnifiers.…”
Section: Introductionmentioning
confidence: 99%